The Impact Of Natural Science Contextual Teaching On Through Project Method Reviewed From Analytical Skill To Students’ Achievementin MTsn Miri Sragen - Anik Sunarsih; Sukarmin Sukarmin; Widha Sunarno (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The aims of this research are to describe the impact of the interaction between teaching method and students’ analytical skill to students’ achievement. The populations are the students of VII class of MTsN Negeri Miri on the teaching period of 2016/2017. This research used Cluster Random Sampling technique as the method to collect the sample. This research was designed using contextual teaching through project method, which teaching method as an independent variable and analytical skill as moderator independent variable. Based on the analysis, it can be concluded that: there is an interaction between teaching method and analytical skill to students’ achievement with the value Fabs=5,549 and the significant number 4,04 (p<0,05). Based on the founding, contextual teaching through the project is one of the methods that give positive impact to increase students’ achievement on a natural science lesson. The increasing of students’ analytical skill is due to the transparency in problem delivering and the responsibility given to a student to search for the solution through a project.